LOCAL OCCURRENCE OF ARTEMISIA CHAMAEMELIFOLIA VILL. IN BULGARIA - PEDASHENKO, H.; VASSILEV, K.; APOSTOLOVA, IVA (Annali di Botanica, 2010)
The current study revealed new data about the rare and relict species Artemisia chamaemelifolia in the country. The data comprise 36 relevés collected in 2008 following the floristic-ecological approach. A. chamaemelifolia communities in Bulgaria have not been studied so far. A new association Galio lovcense-Artemisietum chamaemelifoliae referred to the Cirsio-Brachypodion pinnati alliance is described. The association is distributed locally in the western part of the Balkan Range. Information about different syntaxa including A. chamaemelifolia from the whole range of the species is gathered as well as their ecological characteristics.